Rapid in vivo measurement of β-amyloid reveals biphasic clearance kinetics in an Alzheimer’s mouse model - Yuede, Carla M. (J Exp Med, 2016)
Findings from genetic, animal model, and human studies support the observation that accumulation of the β-amyloid (Aβ) peptide in the brain plays a central role in the pathogenic cascade of Alzheimer’s disease (AD). Human studies suggest that one key factor leading to accumulation is a defect in brain Aβ clearance. We have developed a novel microimmunoelectrode (MIE) to study the kinetics of Aβ clearance using an electrochemical approach. This is the first study using MIEs in vivo to measure rapid changes in Aβ levels in the brains of living mice. Extracellular, interstitial fluid (ISF) Aβ levels were measured in the hippocampus of APP/PS1 mice. Baseline levels of Aβ(40) in the ISF are relatively stable and begin to decline within minutes of blocking Aβ production with a γ-secretase inhibitor. Pretreatment with a P-glycoprotein inhibitor, which blocks blood–brain barrier transport of Aβ, resulted in significant prolongation of Aβ(40) half-life, but only in the latter phase of Aβ clearance from the ISF.